Impulsive versus premeditated aggression in the prediction of violent criminal recidivism. Issue 4 (8th July 2014) - Swogger, Marc T.; Walsh, Zach; Christie, Michael; Priddy, Brittany M.; Conner, Kenneth R.
Abstract : Past aggression is a potent predictor of future aggression and informs the prediction of violent criminal recidivism. However, aggression is a heterogeneous construct and different types of aggression may confer different levels of risk for future violence. In this prospective study of 91 adults in a pretrial diversion program, we examined (a) premeditated versus impulsive aggression in the prediction of violent recidivism during a one‐year follow‐up period, and (b) whether either type of aggression would have incremental validity in the prediction of violent recidivism after taking into account frequency of past general aggression. Findings indicate that premeditated, but not impulsive, aggression predicts violent recidivism. Moreover, premeditated aggression remained a predictor of recidivism even with general aggression frequency in the model. Results provide preliminary evidence that the assessment of premeditated aggression provides relevant information for the management of violent offenders. Aggr. Behav. 41:346–352, 2015. © 2014 Wiley Periodicals, Inc.